Effect of sock knitting maintenance costs on general production costs - (:unkn) unknown (TEXTILE INST, 2004)
Textiles and apparels together are the biggest industry in Turkey which represents Over 60% of the overall exports and 14 play a very important role in the Turkish economy. Since the 1980's Turkish Textile and Apparel Industry have been growing rapidly and has become a force to be considered in the world textile trade. The Turkish sock knitting sector is one of these within textiles which has improved tremendously, since 1980 and become the 3rd largest sock exporter of the world. Maintenance and servicing of the sock knitting machines are directly related to the quality of the sock production and should not to be considered an addition to the cost and as a result increase the price of the product. The aim of this work is to investigate the maintenance, repair and revision approaches of the Turkish sock knitting industry and assess the relations between stoppage due to servicing time and machine breakage time and finally to see the effects of these on the production costs.